POTENTIAL OF PROSECUTING TERRORISM BASED ON THE STATUTE OF THE INTERNATIONAL CRIMINAL COURT - Pilisy, Bence (Faculty of Law Sriwijaya University, 2025)
Terrorism can take many forms, making it particularly challenging to combat. The International Criminal Court (ICC) has been given a prominent role in the fight against terrorism but due to several reasons, the work of the board encounters obstacles. The aim of the research is to demonstrate whether the International Criminal Court (ICC) effectively fights against international terrorism. During the research, an explanatory research method was used, and with the results obtained, the analyze can be conluded that there are several obstacles facing the ICC in the fight against terrorism, the solution of which will take a long time, and the effectiveness of the ICC depends to a large extent on the fact that the missing great powers also join the Statute. Until this happens, the effectiveness of the ICC's activities can be questioned.